Tobacco Endgame: An economic justification for ending the Tobacco Epidemic in Malaysia - Utit, Chakrin; Thinng, Wency Bui Kher (International journal of economic perspectives, 2026)
The 150th session of the WHO’s executive board meeting in Geneva witnessed Malaysia’s stance on passing legislation to bring about a generational endgame to smoking by making the sale of tobacco products illegal to individuals born after 2007. Nevertheless, the policy move was opposed mainly by tobacco-related multinational corporations, putting forward their stand as a responsible industry contributing to economic growth. Therefore, this study assessed the contribution of the tobacco industry to Malaysia’s economy to justify the relevance of the endgame strategy. An initial viewpoint based on the industry’s developmental progress indicated that tobacco had not significantly contributed towards growth. Based on the input-output modelling technique, the findings from the input content and multiplier impact analyses substantiated this view, showing a mismatch between the industry’s potential impacts and its actual contribution. The results also showed that the industry’s growth prospects were unsustainable in the long term since the industry’s integration with its domestic input suppliers relied mainly on contract-farming practices. Therefore, Malaysia’s tobacco endgame strategy implementation is justified based on the study’s findings.